Subclasses of Bi-Univalent Functions of Complex Order Based on Subordination Conditions Involving Wright Hypergeometric Functions - Murugusundaramoorthy Gangadharan (Institute for Research and Community Services (LPPM) ITB, 2015)
In this paper, we introduce and investigate a new subclass of bi-univalent functions Î£ of complex order dened in the open unit disk, which are associated with hypergeometric functions and satisfying subordinate conditions. Furthermore, we nd estimates on the Taylor-Maclaurin coecients | a2 | and | a3 | for functions in the new subclass. Several (known or new) consequences of the results are also pointed out.